A comparative study on COVID-19 disease severity and outcome among patients admitted before and after vaccination at tertiary care hospital - Narayan Mood; Surendra Babu Darivemula; Sreeram Shravani; Kotte Kavyasri; J Ravi Kiran (Journal of Family Medicine and Primary Care, 2023)
Background: Coronavirus disease 2019 (COVID-19) is a novel infectious disease caused by SARS CoV-2 that emerged in Wuhan, China, and has rapidly spread worldwide. The mortality rate of critically ill COVID-19 patients is high. The objective of the study was to assess the COVID-19 disease severity and outcome among COVID-19 positive patients admitted before and after vaccination. Methodology: A prospective observational study conducted among all patients aged more than 18 years were included in the study. The patients who were positive before vaccination and received at least one dose of vaccine and positive after receiving two doses of vaccination included in the study. Disease severity was assessed in terms of high-resolution computed tomography (HRCT) score, intensive care unit (ICU) admission, SpO2 maintained, oxygen, plasma exchange, steroids received and on mechanical ventilation, and outcome was assessed on prognosis and stabilized/discharged to home. Results: A total of 172 were participated in the study with 101 (58.7%) males and 71 (41.3) females, respectively. Amongst them, 92 were affected before vaccination and 80 were affected before vaccination. The patients admitted in the ICU were 56 (32.6%) and 116 (67.4%) were not admitted in the ICU; among the patient admitted in ICU 42 (45.7%) before vaccination, and 14 (17.5%) were after vaccination, and difference was statistically significant with P- value <0.001. SPO2, steroids given, plasma exchange, oxygen >10 litres given and mechanical ventilation were positively associated with the vaccine received and disease severity with P- value <0.05. Conclusion: The severe COVID-19 had the worst outcome in the unvaccinated patients in terms of severity. Most partially vaccinated patients got infected before developing immunity; receiving at least one vaccination dose significantly reduced illness severity.